2021
DOI: 10.1007/s00018-021-04009-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lectin BambL acts as a B cell superantigen

Abstract: B cell superantigens crosslink conserved domains of B cell receptors (BCRs) and cause dysregulated, polyclonal B cell activation irrespective of normal BCR-antigen complementarity. The cells typically succumb to activation-induced cell death, which can impede the adaptive immune response and favor infection. In the present study, we demonstrate that the fucose-binding lectin of Burkholderia ambifaria, BambL, bears functional resemblance to B cell superantigens. By engaging surface glycans, the bacterial lectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…In silico mutagenesis revealed that residues Arg17, Glu28, Trp76, Trp81 in intramonomeric binding sites are crucial for LecF interactions with Me-α-L-fucoside [61]. In the opportunistic human pathogen B. ambifaria , BambL functions as a B cell superantigen binding fucose on blood B cell receptors, possibly triggering activation- induced cell death and disrupting the adaptive immune response [62,63]. Lectin interactions with surface glycans on eukaryotic hosts are evidently important for pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In silico mutagenesis revealed that residues Arg17, Glu28, Trp76, Trp81 in intramonomeric binding sites are crucial for LecF interactions with Me-α-L-fucoside [61]. In the opportunistic human pathogen B. ambifaria , BambL functions as a B cell superantigen binding fucose on blood B cell receptors, possibly triggering activation- induced cell death and disrupting the adaptive immune response [62,63]. Lectin interactions with surface glycans on eukaryotic hosts are evidently important for pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…LecB and BambL, a L‐fucose‐binding lectin from Burkholderia ambifaria , induce B cell activation and subsequent cell death in vitro . Injection of BambL into mice leads to polyclonal activation of B cells (Wilhelm et al , 2019 ; Frensch et al , 2021 ), which could thwart an efficient humoral immune response. However, on the whole, the impact of microbial lectins on the immune system has remained poorly studied.…”
Section: Introductionmentioning
confidence: 99%